The Orientalist’s Misrepresentation of the Other in Edward Said’s Orientalism - Guerricha, Banni, Oussama Abdelbasset Hocine; Boudabia, Anes Tahar (university of El-Oued, 2020)
This study is a multidisciplinary work that draws on fields of literature, cultural studies, philosophy, and politics in order to explore the representation of cultural otherness from Western perspective. This work aims to construct an insightful knowledge on the ways from which the Western Orientalist use in his perception and demonstration of the Arab Islamic world. The order of this work articulates three Orientalist representation that contributed in maintaining the misrepresented depictions of the Other in Edward Said literary Orientalism theory in the context of three historical and contemporary events: Western literature where the use of misrepresentation in children‘s literature was also discussed profoundly, the American Policy represented by Donald Trump, and the severity of Islamophobia after 9/11 terrorist attacks, by situating the three selected events within the Orientalist discourse, and by exploring their continuity on postmodern world. Importantly, the research‘s findings have shown that the Orientalist‘s career of misrepresenting the Other has never stopped and took different faces and shapes over the course of history; yet it all served in a single purpose of the ―self-Other‖ conflict which offers authors a new power of representation, and a new stylistics of writing the Other.
Keywords: Donald Trump, Edward Said, Islamophobia, Literature, Misrepresentation